2021
DOI: 10.1016/j.annonc.2021.05.800
|View full text |Cite
|
Sign up to set email alerts
|

VP6-2021: IMpassion050: A phase III study of neoadjuvant atezolizumab + pertuzumab + trastuzumab + chemotherapy (neoadj A + PH + CT) in high-risk, HER2-positive early breast cancer (EBC)

Abstract: This abstract is presented as part of the ESMO Virtual Plenaries programme (https://www.esmo.org/meetings/esmovirtual-plenaries) and eligible for encore presentation at the ESMO 2021 Congress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…•High incidence of adverse events •Not all patients express PDL1 •No increasing pCR in combination with chemotherapy drugs (10)(11)(12)(13)(14)(15) PDL1: atezolizumab, durvalumab…”
Section: Fdaapprovedmentioning
confidence: 99%
See 1 more Smart Citation
“…•High incidence of adverse events •Not all patients express PDL1 •No increasing pCR in combination with chemotherapy drugs (10)(11)(12)(13)(14)(15) PDL1: atezolizumab, durvalumab…”
Section: Fdaapprovedmentioning
confidence: 99%
“…In the neoadjuvant phase, patients with Grade 3/4 or more serious AEs were increased in the atezolizumab group. There were 4 patients with Grade 5 AEs, including alveolitis, septic shock, sepsis, and COVID-19, in the neoadjuvant phase and 1 patient in the adjuvant phase (11).…”
Section: Immune Checkpoint Inhibitors and Clinical Trials In Tnbcmentioning
confidence: 99%
“…133 The recently released data from the primary analysis of the IMpassion050 study showed no benefit from adding atezolizumab to preoperative atezolizumab plus pertuzumab, trastuzumab, and chemotherapy in terms of pCR both in the overall population and PD-L1-positive tumors (62.4% in the atezolizumab arm versus 62.7% in the placebo arm). 126 Given the high heterogeneity of TNBC, it is opportune to conceive biology-driven clinical trials wherein patients may be treated based on their specific tumor molecular profile.…”
Section: Her2-positive Early Breast Cancermentioning
confidence: 99%
“…In addition, low RAD51 scores, high tumor-infiltrating lymphocytes (TILs), and high programmed death–ligand 1 (PD-L1) expression levels correlate to the olaparib response. 126 An exploratory study of the RIO trial (EudraCT 2014-003319-12) in treatment-naïve patients with early-stage TNBC who received the PARP inhibitor rucaparib showed that 75% of tumors with known homologous recombination repair alterations had low RAD51 foci at baseline. Of the HRD-positive tumors, 70% had low RAD51 foci, while none of the HRD-negative tumors had low RAD51 foci.…”
Section: (Neo)adjuvant Model As a Platform For Research And Innovativ...mentioning
confidence: 99%
“… 31 Conversely the IMpassion050, a Phase 3 study that assessed HER2 targeted therapy, chemotherapy with or without atezolizumab in the neoadjuvant setting, showed no increase of pathologic complete response with the addition of atezolizumab, regardless of the PD-L1 status. 32 There are currently no ICIs approved for the treatment of HER2+ breast cancer, although there are ongoing studies assessing the role of ICIs in selected HER2+ and PD-L1+ tumors. The combination of margetuximab with ICIs represents an attractive option to enhance immunity of tumors traditionally considered immunologically quiescent especially since safety data are available for this combination in gastrointestinal malignancies.…”
Section: Introductionmentioning
confidence: 99%